AMS SoC Formal Verification based on Hybrid Scheme - S.M. Ramesh; B. Gomathy; T.V.P. Sundararajan (International Journal of Engineering and Management Research, 2018)
This paper proposes for AMS SoC formal verification based on Hybrid Scheme combined with symbolic computing and LHPN model, FV-HS. The paper is concerned with a class of AMS designs, continuous-time AMS designs i.e., tunnel diode oscillator for research target. Firstly, Labeled Hybrid Petri Net model is established for safety property verification of tunnel diode oscillator, then mathematical expression for this model is extracted for efficiency enhancement, and then proof policy built in computer algebra Maple is applied to the corresponding LHPN model for tunnel diode oscillator to verify the property. The proposed method is implemented on tunnel diode oscillator and experiment results demonstrate the advantages of the proposed method over previous method. The proposed method overcomes the drawbacks of LHPN, makes full use of the merits of LHPN and symbolic computing, simplifies the workflow of algorithm and enhances the efficiency.